Prevalensi Konstipasi Pada Ibu Hamil - Fransisca Retno Asih (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
Constipation is a complaint of the gastrointestinal system that is commonly experienced by pregnant women, which can affect physical, psychological, social health, and quality of life. There has been no research related to the prevalence of pregnancy constipation in Banyuwangi. This study aims to provide an overview of the prevalence of constipation in pregnant women based on the Rome II criteria. This research method was descriptive with a cross sectional approach to 715 pregnant women with gestational age of 13-16 weeks, 27-30 weeks, and 36-39 weeks, singleton pregnancies, and became research respondents in five primary health care facilities in Banyuwangi. Pregnant women who met the criteria and came to the primary health care facilities sequentially (consecutive sampling) were given a questionnaire containing seven questions about symptoms of constipation according to the Rome II criteria. The results of the study were 17.8% of 715 pregnant women were constipated. The prevalence of constipation in the third trimester (19.3%) was higher than in the first (17.3%) and second trimester (16.4%). Pregnant women who are working, highly educated, and primigravida show a higher prevalence of constipation. The conclusion of the study is that constipation in all trimesters of large pregnancy is characterized by the consistency of hard and strong stools at one time in four defecations for four weeks. Constipation screening and counseling is important for midwives at the initial contact, especially in first-level of health facilities. Keywords: Constipation, Pregnant Women